2022
DOI: 10.20944/preprints202205.0304.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Event-Based Emergency Detection for Safe Drone

Abstract: Quadrotor drones have rapidly gained interest recently. Numerous studies are underway for the commercial use of autonomous drones, and especially the distribution businesses are taking serious reviews on drone delivery services. However, there are still many concerns about urban drone operations. The risk of failures and accidents makes it difficult to provide drone-based services in the real world with ease. There have been many studies that introduced supplementary methods to handle drone failures and emerge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The introduced enhancements involve the incorporation of Multi-Scale Image Fusion and the integration of the P2 Layer into the medium-size model (M-model) of YOLO-V8. The proposed model underwent evaluation in the 6th WOSDETC challenge, providing a practical assessment of its performance in real-world scenarios [14].…”
Section: Related Workmentioning
confidence: 99%
“…The introduced enhancements involve the incorporation of Multi-Scale Image Fusion and the integration of the P2 Layer into the medium-size model (M-model) of YOLO-V8. The proposed model underwent evaluation in the 6th WOSDETC challenge, providing a practical assessment of its performance in real-world scenarios [14].…”
Section: Related Workmentioning
confidence: 99%
“…Such methods use the idea of regression-based methods to directly regress the coordinates of the area frame and object class at this location among multiple locations of the input image. In target detection tasks, the YOLO series algorithms have been popular in various research, and with the latest YOLOv8 [8] series, they have shown excellent performance in the field of target de-tection. This work provides an enhanced YOLOv8 algorithm based on the industrial UAV target detection job and obtains good results on the UAV dataset VisDrone2021.This paper's primary contributions are as follows:…”
Section: Introductionmentioning
confidence: 99%